Composite deodorant as well as preparation method and application thereof

By using modified porous adsorption protection powder, the problems of low efficiency and insufficient stability of existing deodorants were solved, and a composite deodorant with high efficiency antibacterial deodorant performance was prepared, and it was successfully applied to fibers and fabrics, achieving stable and long-lasting deodorant effects.

CN119499425AActive Publication Date: 2025-02-25YUNQI (QINGDAO) MATERIALS TECHNOLOGY CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411476254.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-02-25
Estimated Expiration
2044-10-22

AI Technical Summary

Technical Problem

Existing deodorants are inefficient in efficiency, insufficient stability, and may cause harm to the human body and the environment, making it difficult to play a stable deodorant effect on fabric fibers.

Method used

Modified porous adsorption protection powder is used to improve the stability and functional durability of antibacterial and deodorant substances through physical adsorption and chemical modification, and prepare composite deodorants and apply them to fibers or fabrics.

Benefits of technology

It significantly improves the stability and functional durability of the antibacterial and deodorizing effects of composite deodorants, can effectively reduce the concentration of different types of odors, and meets the needs of multi-purpose and multi-application scenarios.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of adsorbents, and particularly relates to modified porous adsorption protection powder, a composite deodorant and application thereof. The modified porous adsorption protective powder is prepared according to the following steps: performing spray drying on inorganic porous substance dispersion liquid or beta-cyclodextrin organic porous substance dispersion liquid to obtain porous substance powder; hemicellulose and / or polypeptide are / is dissolved in ionic liquid, and a mixed solution with the mass concentration being 2-5% is obtained; and adding porous substance powder into the mixed solution, uniformly stirring and mixing, filtering, adding water, and carrying out spray drying to obtain the modified porous adsorption protective powder. The modified porous adsorption protective powder provided by the invention plays a role in protecting effective active ingredients for resisting bacteria and deodorizing, and the stability and the function durability of the antibacterial effect and the deodorizing effect of the composite deodorant prepared by the method provided by the invention are greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of adsorbents, and specifically relates to a composite deodorant and a preparation method and application thereof. Background Art

[0002] With the continuous development of society and the improvement of people's living standards, people are becoming more and more sensitive to unpleasant odors, which not only affect their sense of smell and emotions, but also seriously affect their physical health. Especially in hot weather or during strenuous exercise, people sweat a lot, and sweat, sebum and other human secretions become a breeding ground for bacteria and pathogenic microorganisms. They are easy to produce odors on clothes and textiles, affecting people's quality of life. Therefore, deodorant products that can quickly and efficiently eliminate odors and have a comfortable smell are becoming more and more popular and become people's first choice. However, traditional deodorants are inefficient, unstable, and may cause varying degrees of damage to the human body and the environment.

[0003] As an adsorbent that can eliminate odor, absorb moisture and remove bacteria, it is not only composed of a surfactant, but also includes an adsorption carrier. In particular, adsorbents that can stably exert a deodorizing effect on fabric fibers are difficult to obtain. Summary of the invention

[0004] The technical problem to be solved by the present invention is to overcome the above-mentioned defects of the prior art and provide a modified porous adsorption protection powder to protect the effective active ingredients of antibacterial and deodorizing properties.

[0005] The present invention also provides a composite deodorant prepared by using the modified porous adsorption protection powder, and the stability and functional durability of the antibacterial and deodorizing effects are greatly improved.

[0006] The composite deodorant prepared by the present invention is directly applied to synthetic fibers by melt spinning, or a composite deodorant dispersion system prepared by the composite deodorant is applied to chemical fibers by wet spinning.

[0007] A composite deodorant: specifically comprising the following steps: a. Preparation of composite deodorizing alkaline powder a1. Add one or more of alginic acid, lactic acid and chlorogenic acid into water at 25-30°C for dissolution to obtain a solution with a mass concentration of 4%-6%; the alginic acid, lactic acid and chlorogenic acid are biological.

[0008] a2. Add the prepared modified porous adsorption protection powder to the solution of step a1, wherein the mass ratio of the modified porous adsorption protection powder to the solution of a1 is 1:20-30, stir and adsorb for 30-50 minutes, and spray dry to obtain the first composite deodorizing alkaline powder; a3. Add the first composite deodorizing alkaline powder to an aqueous solution with a mass concentration of 3%-5% polycarboxylic acid, 1%-3% zinc salt and a temperature of 25°C-35°C, adsorb for 30min-40min, filter, irradiate the solid with electron beam, and vacuum dry to obtain a composite deodorizing alkaline powder; the irradiation dose is 20-50kGy, and the irradiation time is 60-120s, so that the polycarboxylic acid, biological acid, and hydroxyl groups when hemicellulose are used react, and the zinc salt is used to react with part of the biological acid, which not only gives the zinc antibacterial property of the powder, but also increases the stability and functional durability of the composite deodorizing alkaline powder. Then vacuum dry to obtain the final composite deodorizing alkaline powder. The use of polycarboxylic acid can further enhance the deodorizing effect; the polycarboxylic acid is one of butane tetracarboxylic acid, citric acid, and maleic acid, and the zinc salt is one of zinc sulfate or zinc acetate.

[0009] b. Preparation of composite powder for eliminating acid odor and senile odor b1. One or more of amino acids, tannins and polyphenols are mixed and added into water for dissolution to obtain a solution with a mass concentration of 5%-7%; the amino acid is one of glycine, tyrosine, serine and cysteine; the polyphenols are flavonoids and tea polyphenols, etc., wherein the flavonoids are one of flavonols, flavanones, flavanols and isoflavanones, mainly from plant extracts; tannins include plant extracts such as persimmon tannin and green tea tannin; the reactive groups in the molecules of tannins and polyphenols can have multiple bonding effects with the functional groups in amino acids and protein molecules, thereby preventing the reproduction of bacteria, making them antibacterial, and improving the stability and functional durability of the antibacterial and deodorizing substances; b2. Add the prepared modified porous adsorption protection powder to the solution of step b1, wherein the mass ratio of the modified porous adsorption protection powder to the solution of step a1 is 1:20-30, stir and adsorb for 30-50 min, and spray dry to obtain the first composite powder for eliminating acid odor and senile odor; b3, adding the first composite deodorizing and acid odor removing powder to an aqueous solution of 1.5%-3% ethylene glycol diglycidyl ether or glutamine aminotransferase at a temperature of 25°C-35°C, adsorbing for 20min-30min, filtering, and cross-linking the solid at a reaction temperature of 30°C-40°C, a reaction time of 50min-70min, and a pH of 7.0-8.5. After the reaction, vacuum drying is performed to obtain a composite deodorizing and acid odor removing powder; c. Mix the prepared composite deodorizing powder for alkaline odor removal with the composite deodorizing powder for acidic odor removal and old age odor removal to obtain a composite deodorant. In step c, the prepared composite deodorizing powder for alkaline odor removal with the composite deodorizing powder for acidic odor removal and old age odor removal may be mixed, or a copolymer of 3-hydroxybutyrate and 3-hydroxyvalerate or an aromatic substance may be added to obtain a composite deodorant.

[0010] The modified porous adsorption protection powder of the present invention is prepared according to the following steps: (1) spray-drying an inorganic porous material dispersion or a β-cyclodextrin organic porous material dispersion to obtain a porous material powder; (2) dissolving hemicellulose and / or polypeptide in ionic liquid to obtain a mixed solution with a mass concentration of 2-5%; (3) Add the porous material powder of step (1) to the mixed solution of step (2), wherein the mass ratio of the porous material powder to the mixed solution of step (2) is 1:20-30, stir and mix, and then fully adsorb for 30-50 minutes, filter, add water, and spray dry to obtain a modified porous adsorption protection powder.

[0011] Step (1) The inorganic porous material dispersion is prepared by grinding the inorganic porous material powder to a particle size of D90≤3.350μm, adding a silane coupling agent after dispersion, and uniformly dispersing the powder; the inorganic porous material powder is one of activated carbon, binchotan, silica gel, zeolite, and silicate minerals; the amount of the silane coupling agent added is 10%-15% of the mass of the inorganic porous material powder. The silane coupling agent is one of vinyl triethoxysilane, vinyl trimethoxysilane, and vinyl tri(β-methoxyethoxy)silane. By treating the porous material powder with the silane coupling agent, the necessary reaction groups are provided for the subsequent modification of the inorganic porous material powder with organic matter, thereby improving the stability of the adsorbed material.

[0012] Preferably, the mass concentration of the inorganic porous substance powder in the inorganic porous substance dispersion is 30%-50%; the mass concentration of β-cyclodextrin in the β-cyclodextrin organic porous substance dispersion is 30%-50%.

[0013] In step (2), the degree of polymerization of hemicellulose is 50-80; the number average molecular weight of the polypeptide is 5000-10000; the ionic liquid is an alkyl imidazole type ionic liquid, wherein the cation is one of ethyl and butyl; the anion is Cl - 、SCN - One of them. Hemicellulose and polypeptides have more hydrophilic groups, and the porous material is modified to improve its hygroscopicity, which is convenient for the subsequent full adsorption of functional substances. At the same time, it provides a cross-linked matrix for subsequent adsorption in the pores to increase its stability.

[0014] The spray drying parameters in step (1) and step (3) are: inlet air temperature 150°C-180°C, outlet air temperature 95°C-105°C, feed rate 15mL / min-25mL / min. The porous material powder obtained by spray drying has a good degree of dispersion and relatively uniform particles.

[0015] Application of the composite deodorant: the prepared composite deodorant is used in synthetic fibers by melt spinning, or the composite deodorant is used to make a composite deodorant dispersion for use in chemical fibers by wet spinning, or the composite deodorant dispersion is directly applied to fabrics and the fabrics are treated by a padding process.

[0016] The specific steps of using the composite deodorant to prepare the composite deodorant dispersion are as follows: adding the prepared composite deodorant to water, the mass fraction of which is 35%-45%, and adding a dispersant accounting for 15%-20% of the mass of the composite deodorant and a defoamer accounting for 2%-5% of the mass of the composite deodorant, stirring and mixing evenly to disperse, and then adding a thickener accounting for 3%-6% of the mass of the composite deodorant, stirring evenly, and preparing the composite deodorant dispersion. The dispersion speed is 1500r / min-2000r / min, the temperature is maintained at 18℃-20℃ during the dispersion process, and the dispersion time is 60min-90min. The dispersant is one of sodium dodecylbenzene sulfonate and sodium hexametaphosphate; the defoamer is one of polyoxypropylene polyoxyethylene glycerol ether and polyoxypropylene glycerol ether; the thickener is one of sodium alginate, polyvinyl pyrrolidone and sodium carboxymethyl cellulose, so as to increase the viscosity of the dispersion system, thereby improving its dispersion stability.

[0017] Specifically, the steps are divided into the following processes: 1. Preparation of modified porous adsorption protection powder 1) Preparation of porous material powder Inorganic porous materials such as activated carbon, binchotan, silica gel, zeolite and silicate minerals are ground and dispersed in water using a sand mill disperser, wherein the zirconium ball filling rate is 50%-80%, the concentration of the inorganic porous material is 30%-50%, and the grinding speed is 2000-3000r / min. During the grinding process, the particle size of the inorganic porous material powder is detected until the particle size reaches D90≤2.950μm, thereby obtaining a primary inorganic porous material powder dispersion; and a silane coupling agent is added to the inorganic porous material powder dispersion to modify its surface, and the added amount is 10%-15% of the inorganic porous material powder. The reaction is continued at a speed of 5000r / min-650r / min for 30min-50min, thereby obtaining a final inorganic porous material dispersion.

[0018] Alternatively, the organic porous dispersed substance β-cyclodextrin is directly dispersed in water to obtain a β-cyclodextrin organic porous dispersed substance dispersion liquid with a concentration of 30%-50%.

[0019] The inorganic porous material dispersion or organic porous dispersed material dispersion prepared above is dried by a spray dryer using a spray drying method, wherein the inlet air temperature is 150°C-180°C, the outlet air temperature is 95°C-105°C, and the feed rate is 15mL / min-25mL / min to obtain a porous material powder.

[0020] 2) Preparation of modified porous adsorption protection powder Hemicellulose with a degree of polymerization of 50-80 or a high molecular weight polypeptide with a molecular weight of 5000-10000 or a mixture of the two in any proportion is dissolved in an ionic liquid to obtain a hemicellulose or polypeptide solution or a mixture of the two with a concentration of 2%-5%.

[0021] The prepared porous material powder is added to the prepared solution prepared above, and stirring is performed during the adding process, and the stirring speed is 300r / min-350r / min. After the addition is completed, stirring is continued for 30min-50min, so that the above porous material fully absorbs the solution, and then filtered to obtain a wet modified porous material, and then deionized water is added to the wet modified porous material to precipitate the adsorbed hemicellulose or polypeptide and adhere to the pore surface of the porous material, and then spray drying is performed, wherein the inlet air temperature is 150℃-180℃, the outlet air temperature is 95℃-105℃, and the feed rate is 15mL / min-25mL / min to obtain a modified porous adsorption protection powder.

[0022] 2. Preparation of composite alkaline deodorizing powder One or more of biological alginic acid, lactic acid, and chlorogenic acid are added to deionized water at 25°C-30°C in any proportion to dissolve to obtain a solution with a concentration of 4%-6%, and then the prepared modified porous adsorption protection powder is added to the above solution for adsorption. Stirring is started during the addition of the modified porous adsorption protection powder and adsorption, and the stirring speed is 200r / min-300r / min. After the addition is completed, stirring is continued for 30min-50min to fully absorb the biological acid, and the mixture is dried by a spray drying process to obtain the first composite deodorizing alkaline powder.

[0023] Then, the first composite deodorizing alkaline powder is added to a solution containing 3%-5% polycarboxylic acid, 1%-3% zinc salt and the temperature is 25°C-35°C, and the adsorption is continued for 30min-40min. After the adsorption, the solid is filtered and the filtered solid is irradiated with an electron beam with an irradiation dose of 20kGy-50kGy and an irradiation time of 60s-120s, and then vacuum dried to obtain a composite deodorizing alkaline powder.

[0024] 3. Preparation of composite powder for eliminating acidic odor and senile odor One or more of amino acids, tannins and polyphenols are added to deionized water in any proportion to dissolve, and a solution with a concentration of 5%-7% is obtained. Then the prepared modified porous adsorption protection powder is added to the above solution for adsorption. Stirring is started during the addition of the modified porous adsorption protection powder and adsorption, and the stirring speed is 200r / min-300r / min. After the addition is completed, stirring is continued for 30min-50min to allow sufficient adsorption, and the powder is dried by spray drying process to obtain the first composite powder for eliminating acid odor and old age odor.

[0025] Then, the first composite powder for removing acidic odor and old age odor is added to a solution containing 1.5%-3% of a cross-linking agent ethylene glycol diglycidyl ether or glutamine aminotransferase at a temperature of 25-35°C, and adsorption is continued for a treatment time of 20min-30min. After adsorption and filtration, a cross-linking reaction is performed on the filtered solid at a reaction temperature of 30°C-40°C, a reaction time of 50min-70min, a pH of 7.0-8.5, and vacuum drying is performed to obtain a composite powder for removing acidic odor and old age odor.

[0026] 4. Preparation and application of composite deodorant The prepared composite alkaline deodorizing powder and the composite acidic and old age deodorizing powder are mixed in any proportion, preferably in a ratio of 1:1-1:2. They can also be blended with PHBV (a copolymer of 3-hydroxybutyrate and 3-hydroxyvalerate) or aromatic substances such as lavender to obtain a composite deodorant.

[0027] The prepared antibacterial composite absorbent powder contains natural or plant substances or is prepared therefrom, has antibacterial effect, is harmless to the human body, and further enhances its function through cross-linking and metal complexation, and has good effects on acidic odors (acetic acid, isovaleric acid, etc.), alkaline odors (ammonia, trimethylamine, etc.) and senile odors (2-nonenal, etc.). The prepared antibacterial composite absorbent powder has an inhibition rate of ≥97.5% against Staphylococcus aureus, ≥98.9% against Escherichia coli, and ≥98.1% against Candida albicans (GB / T20944.3-2008 "Evaluation of Antibacterial Properties of Textiles Part 3: Oscillation Method"); its ammonia reduction rate is ≥96.1%, acetic acid reduction rate is ≥97.5% (GB / T33610.2-2017 Determination of Deodorizing Performance of Textiles Part 2: Detection Tube Method), isovaleric acid reduction rate is ≥99.6%, and 2-nonenal reduction rate is ≥98.3% (GB / T33610.3-2019 Determination of Deodorizing Performance of Textiles Part 3: Gas Chromatography).

[0028] The prepared composite deodorant is used for melt-spinning synthetic fibers, and is first used to prepare synthetic fiber masterbatch. The addition amount of the composite deodorant powder in the final fiber is 6.0%-8.0%.

[0029] 5. Preparation and application of composite deodorant dispersion The prepared composite deodorant is added to deionized water with a mass fraction of 35%-45%, and a dispersant accounting for 15%-20% of the mass of the composite deodorant and a defoamer accounting for 2%-5% of the mass of the composite deodorant are added to the system. After stirring and mixing evenly, the mixture is added into a high-speed dispersant for dispersion at a dispersion speed of 1500-2000 r / min. During the dispersion process, the temperature is maintained at 18-20°C for a dispersion time of 60-90 min. Then, a thickener accounting for 3%-6% of the mass of the composite deodorant is added and mixed evenly to obtain a composite deodorant dispersion.

[0030] The composite deodorant dispersion prepared by the present invention is used for wet-spun chemical fibers, and the addition amount calculated by the effective components is 4.0%-6.0%; at the same time, the composite deodorant dispersion can be used to treat the fabric through a padding process to obtain a deodorizing fabric, and different ratios can be used according to different application fields, and the final total addition amount is 7.0%-10.0%.

[0031] The fiber or fabric prepared by the present invention has an antibacterial rate of ≥81.2% against Staphylococcus aureus, an antibacterial rate of ≥82.5% against Escherichia coli, and an antibacterial rate of ≥83.3% against Candida albicans (GB / T20944.3-2008 "Evaluation of Antibacterial Properties of Textiles Part 3: Oscillation Method"); its ammonia reduction rate is ≥79.5%, the acetic acid reduction rate is ≥76.9% (GB / T 33610.2-2017 Determination of Deodorizing Performance of Textiles Part 2: Detection Tube Method), the isovaleric acid reduction rate is ≥88.5%, and the 2-nonenal reduction rate is ≥77.5% (GB / T33610.3-2019 Determination of Deodorizing Performance of Textiles Part 3: Gas Chromatography).

[0032] In view of the shortcomings of the prior art, the composite deodorant of the present invention adopts multiple mechanisms. First, porous substances are selected, which not only protect the antibacterial and deodorizing substances, but also adsorb the odor through the physical adsorption of the porous substances, reduce the concentration of the odor, and thus achieve the effect of physical deodorization. Secondly, according to different odor mechanisms such as acid-base neutralization and oxidation, different antibacterial and deodorizing substances are prepared, and modified to improve stability and functional durability. Different odors such as ammonia, acetic acid, isovaleric acid and old age odor can be treated, and can also be modified by adding aromatic substances, thereby meeting the needs of multi-purpose and multi-application scenarios.

[0033] Compared with the prior art, the present invention has the following beneficial effects: (1) The composite deodorant of the present invention adopts multiple mechanisms. First, porous materials are selected, which not only protect the antibacterial and deodorizing substances, but also achieve the effect of physical deodorization through physical adsorption of the porous materials. Secondly, different antibacterial and deodorizing substances are prepared according to different odor mechanisms, and modified to improve stability and functional durability. Different odors can be treated, meeting the needs of multi-purpose and multi-application scenarios.

[0034] (2) The present invention first uses a silane coupling agent to treat the porous material powder, which provides the necessary reaction groups for the subsequent modification of the inorganic porous material powder with a hydrophilic substance, thereby improving the stability of the adsorbed substance. At the same time, the porous material is modified by using hemicellulose and polypeptides with more hydrophilic groups to improve its hygroscopicity, which facilitates the subsequent full adsorption of more functional substances. At the same time, a cross-linked matrix is ​​provided for subsequent adsorption in the pores, which interacts with the antibacterial and deodorizing substances by chemical bonds, thereby increasing the stability and functional durability of the functional substances.

[0035] (3) The composite deodorant prepared by the present invention contains natural or plant substances or is prepared from the same, which have antibacterial effects and are harmless to the human body. Moreover, the function is further enhanced through cross-linking and metal complexation.

[0036] (4) The present invention uses different porous materials and different functional antibacterial and deodorizing agents to give the fiber different colors, such as black (activated carbon, binchotan charcoal, etc.), white and yellow, etc., to meet the needs of multiple colors.

[0037] (5) The antibacterial and deodorizing agent prepared by the present invention can be used for the preparation of chemical fibers, including chemical fibers produced by wet spinning and synthetic fibers produced by melt spinning. The antibacterial and deodorizing agent can also be used to treat fabrics through a padding process to obtain antibacterial and deodorizing fabrics. Different ratios can be used according to different application fields. DETAILED DESCRIPTION

[0039] The present invention will be further described below in conjunction with specific embodiments.

[0040] The raw materials and additives used in the following examples and comparative examples are all normal commercially available products.

[0041] Example 1 1. The preparation of modified porous adsorption protection powder includes the following steps: 1) Preparation of porous material powder The Binchotan inorganic porous material is ground and dispersed by using a sand mill disperser, wherein the zirconium ball filling rate is 50%, the concentration of the inorganic porous material is 30%, and the grinding speed is 2000r / min. During the grinding process, the particle size of the inorganic porous material powder is detected until the particle size reaches D90=2.950μm, thereby obtaining a primary inorganic porous material powder dispersion; and a silane coupling agent vinyl triethoxysilane is added to the inorganic porous material powder dispersion for surface modification treatment, and the added amount is 10% of the inorganic porous material powder. The reaction is continued at a speed of 500r / min for 30min to obtain an inorganic porous material powder dispersion.

[0042] The inorganic porous material dispersion prepared above was dried using a spray dryer with an air inlet temperature of 150° C., an air outlet temperature of 95° C., and a feed rate of 15 mL / min to obtain porous material powder.

[0043] 2) Preparation of modified porous adsorption protection powder Hemicellulose with a degree of polymerization of 80 is dissolved in an ionic liquid to obtain a hemicellulose solution with a concentration of 2%. The ionic liquid is an alkyl imidazole type ionic liquid, wherein the cation is ethyl and the anion is Cl - .

[0044] The prepared porous material powder is added to the prepared solution prepared above, and stirring is carried out during the adding process. The stirring speed is 300r / min. After the addition is completed, stirring is continued for 30 minutes to allow the porous material to fully absorb the solution, and then filtered to obtain a wet modified porous material. Deionized water is added to the wet modified porous material to allow the adsorbed hemicellulose to precipitate and adhere to the pore surface of the porous material, and then spray drying is carried out, wherein the inlet air temperature is 150°C, the outlet air temperature is 95°C, and the feed rate is 15mL / min to obtain a modified porous adsorption protection powder.

[0045] 2. A composite deodorant: It is prepared by using the modified porous adsorption protection powder, and specifically comprises the following steps: a. Preparation of composite deodorizing alkaline powder a1. Add biological alginic acid into deionized water at 25°C to dissolve it to obtain a solution with a concentration of 4%.

[0046] a2. Add the prepared modified porous adsorption protection powder into the above solution for adsorption. Start stirring during the addition of the modified porous adsorption protection powder and adsorption. The stirring speed is 200r / min. After the addition is completed, continue stirring for 30 minutes to allow it to fully absorb the biological acid. Dry it using a spray drying process to obtain the first composite deodorizing alkaline powder.

[0047] a3. Add the first composite deodorizing alkaline powder to a solution containing 3% butanetetracarboxylic acid and 1% zinc sulfate at a temperature of 25°C, and continue adsorption for 30 minutes. After adsorption, filter and irradiate the filtered solid with electron beam at a dose of 20 kGy for 120 seconds, and then vacuum dry to obtain a composite deodorizing alkaline powder.

[0048] b. Preparation of composite powder for eliminating acid odor and senile odor b1. Add glycine and persimmon tannin into deionized water at a mass ratio of 1:1 to dissolve them to obtain a solution with a total concentration of 5%.

[0049] b2. Add the prepared modified porous adsorption protection powder into the above solution for adsorption. Start stirring during the addition of the modified porous adsorption protection powder and adsorption. The stirring speed is 200r / min. After the addition is completed, continue stirring for 30 minutes to allow it to be fully adsorbed. Then, dry it using a spray drying process to obtain the first composite powder for eliminating acid odor and old age odor.

[0050] b3. Add the first composite acidic and old age odor eliminating powder into a solution containing 1.5% of a cross-linking agent ethylene glycol diglycidyl ether at a temperature of 25°C, and continue adsorption for 20 minutes. After adsorption and filtration, cross-link the filtered solid at a reaction temperature of 30°C, a reaction time of 70 minutes, and a pH of 7.0. Then, vacuum drying is performed to obtain the final composite acidic and old age odor eliminating powder.

[0051] c. The prepared composite alkaline deodorizing powder and the composite acidic and old age deodorizing powder are mixed in a mass ratio of 1:1 to prepare a composite deodorant.

[0052] The prepared antibacterial composite absorbent powder has an inhibition rate of 97.5% against Staphylococcus aureus, 98.9% against Escherichia coli, and 98.1% against Candida albicans; its ammonia reduction rate is 96.1%, acetic acid reduction rate is 97.5%, isovaleric acid reduction rate is 99.6%, and 2-nonenal reduction rate is 98.3%.

[0053] d. Add the prepared composite deodorant into deionized water with a mass fraction of 35%, and add 15% of the mass of the composite deodorant dispersant sodium dodecylbenzene sulfonate and 2% of the mass of the composite deodorant defoaming agent polyoxypropylene polyoxyethylene glycerol ether to the system. After stirring and mixing evenly, add the mixture into a high-speed disperser for dispersion at a speed of 1500 r / min. During the dispersion process, maintain the temperature at 18°C ​​for 90 min. Then, add 3% of the mass of the composite deodorant as a thickener sodium alginate and mix well to obtain a composite deodorant dispersion.

[0054] The prepared composite deodorant dispersion was added to the viscose fiber used in the wet spinning process through the pre-spinning injection process, and the addition amount was 6.0% (to cellulose methyl cellulose) according to the effective ingredients. Then, after cutting, washing, desulfurization, bleaching, oiling, drying and other processes, the viscose staple fiber with antibacterial and deodorizing functions of 1.67 dtex×38 mm was obtained. The fiber has an antibacterial rate of 81.2% against Staphylococcus aureus, 82.5% against Escherichia coli, and 83.3% against Candida albicans; its ammonia reduction rate is 79.5%, acetic acid reduction rate is 76.9%, isovaleric acid reduction rate is 88.5%, and 2-nonenal reduction rate is 77.5%.

[0055] Example 2 1. The preparation of modified porous adsorption protection powder includes the following steps: 1) Preparation of porous material powder The zeolite porous material was ground and dispersed by using a sand mill disperser, wherein the zirconium ball filling rate was 68%, the concentration of the inorganic porous material was 39.5%, and the grinding speed was 2560r / min. During the grinding process, the particle size of the inorganic porous material powder was detected until the particle size reached D90=2.736μm, thereby obtaining a primary inorganic porous material powder dispersion. Silane coupling agent vinyltrimethoxysilane was added to the inorganic porous material powder dispersion for surface modification, and the added amount was 12.6% of the inorganic porous material powder. The reaction was continued at a speed of 592r / min for 41min to obtain an inorganic porous material powder dispersion.

[0056] The inorganic porous material dispersion prepared above was dried using a spray dryer with an air inlet temperature of 168° C., an air outlet temperature of 99.5° C., and a feed rate of 20.5 mL / min to obtain porous material powder.

[0057] 2) Preparation of modified porous adsorption protection powder A high molecular weight polypeptide with a molecular weight of 7500 was dissolved in an ionic liquid to obtain a polypeptide solution with a concentration of 3.6%. The ionic liquid is an alkyl imidazole type ionic liquid, wherein the cation is butyl; the anion is SCN - .

[0058] The prepared porous substance powder is added to the prepared solution, and stirring is performed during the addition process, and the stirring speed is 326r / min. After the addition is completed, stirring is continued for 42 minutes to allow the porous substance to fully absorb the solution, and then filtered to obtain a wet modified porous substance, and then deionized water is added to the wet modified porous substance to allow the adsorbed polypeptide to precipitate and adhere to the pore surface of the porous substance, and then spray drying is performed, wherein the inlet air temperature is 168°C, the outlet air temperature is 99°C, and the feed rate is 21mL / min, so that a modified porous adsorption protection powder is obtained.

[0059] 2. A composite deodorant: It is prepared by using the modified porous adsorption protection powder, and specifically comprises the following steps: a. Preparation of composite deodorizing alkaline powder a1. Add biological alginic acid and chlorogenic acid in a mass ratio of 1:1 into deionized water at 28.6° C. to dissolve and obtain a solution with a concentration of 5.1%.

[0060] a2. Add the prepared modified porous adsorption protection powder to the above solution for adsorption. Start stirring during the addition of the modified porous adsorption protection powder and adsorption. The stirring speed is 255r / min. After the addition is completed, continue stirring for 41 minutes to allow it to fully absorb the biological acid. Dry it using a spray drying process to obtain the first composite deodorizing alkaline powder.

[0061] a3. Add the first composite deodorizing alkaline powder to a solution containing 3.9% citric acid, 2.1% zinc acetate and a temperature of 31°C, and continue adsorption for 35 minutes. After adsorption, filter and irradiate the filtered solid with electron beam at a dose of 38 kGy for 91 seconds, and then vacuum dry to obtain the final composite deodorizing alkaline powder.

[0062] b. Preparation of composite powder for eliminating acid odor and senile odor b1. Add green tea tannin and flavonols in a mass ratio of 1:2 into deionized water for dissolution to obtain a solution with a concentration of 6.2%. The flavonols are derived from plant extracts.

[0063] b2. Add the prepared modified porous adsorption protection powder into the above solution for adsorption. Start stirring during the addition of the modified porous adsorption protection powder and adsorption. The stirring speed is 265r / min. After the addition is completed, continue stirring for 41 minutes to allow it to be fully adsorbed. Use a spray drying process to dry it to obtain the first composite powder for eliminating acid odor and old age odor.

[0064] b3. Add the first composite acidic and old age odor eliminating powder into a solution containing 2.6% of the cross-linking agent glutamine transaminase at a temperature of 29°C, and continue adsorption for 26 minutes. After adsorption and filtration, cross-link the filtered solid at a temperature of 35°C, a reaction time of 61 minutes, and a pH of 7.9. Then, vacuum drying is performed to obtain the final composite acidic and old age odor eliminating powder.

[0065] c. The prepared composite alkaline deodorizing powder and the composite acidic and elderly deodorizing powder are mixed in a mass ratio of 1:2, and then PHBV (a copolymer of 3-hydroxybutyrate and 3-hydroxyvalerate) accounting for 10% of the total powder mass is added for blending to prepare a composite deodorant.

[0066] The prepared antibacterial composite absorbent powder has an inhibition rate of 98.6% against Staphylococcus aureus, 99.1% against Escherichia coli, and 98.9% against Candida albicans; its ammonia reduction rate is 98.1%, acetic acid reduction rate is 99.0%, isovaleric acid reduction rate is 99.7%, and 2-nonenal reduction rate is 98.6%.

[0067] The prepared composite deodorant is added to the polyester fiber for melt spinning by pre-spinning injection, and is first used to prepare deodorizing polyester masterbatch slices, and the polyester slice melt and the composite deodorant powder are fully mixed, wherein the composite deodorant powder is added in an amount of 30% (to the polyester slices), and then the deodorizing polyester masterbatch slices and conventional polyester slices are mixed in proportion for melt spinning, so that the addition amount of the composite deodorant powder in the final fiber is 8.0%. Then the fiber is cut, oiled, dried and other processes to obtain a polyester staple fiber with a specification of 2.22dtex×38mm and multifunctional functions such as antibacterial and deodorizing. The fiber has an antibacterial rate of 83.6% against Staphylococcus aureus, an antibacterial rate of 85.1% against Escherichia coli, and an antibacterial rate of 85.3% against Candida albicans; its ammonia reduction rate is 81.6%, acetic acid reduction rate is 79.2%, isovaleric acid reduction rate is 90.1%, and 2-nonenal reduction rate is 79.1%.

[0068] Example 3 1. The preparation of modified porous adsorption protection powder includes the following steps: 1) Preparation of porous material powder The organic porous dispersion material β-cyclodextrin is directly used for dispersion to obtain a β-cyclodextrin organic porous dispersion material dispersion liquid with a concentration of 50%.

[0069] The prepared β-cyclodextrin organic porous dispersed material dispersion was dried using a spray dryer with an inlet air temperature of 180° C., an outlet air temperature of 105° C., and a feed rate of 25 mL / min to obtain a porous material powder.

[0070] 2) Preparation of modified porous adsorption protection powder A mixture of hemicellulose with a degree of polymerization of 50 and a high molecular weight polypeptide with a molecular weight of 5000 is dissolved in an ionic liquid to obtain a 5% concentration of a mixture of hemicellulose and polypeptide. The ionic liquid is an alkyl imidazole type ionic liquid, wherein the cation is butyl; the anion is Cl - .

[0071] The prepared porous substance powder is added to the prepared solution, and the stirring is performed while adding, and the stirring speed is 350r / min. After the addition is completed, the stirring is continued for 50 minutes, so that the porous substance fully absorbs the solution, and then filtered to obtain a wet modified porous substance, and then deionized water is added to the wet modified porous substance to precipitate the adsorbed substance and attach it to the pore surface of the porous substance. Then spray drying is performed, wherein the inlet air temperature is 180°C, the outlet air temperature is 105°C, and the feed rate is 25mL / min, so that a modified porous adsorption protection powder is obtained.

[0072] 2. A composite deodorant: It is prepared by using the modified porous adsorption protection powder, and specifically comprises the following steps: a. Preparation of composite deodorizing alkaline powder a1. Add biological chlorogenic acid into deionized water at 30° C. and dissolve it to obtain a solution with a concentration of 6%.

[0073] a2. Add the prepared modified porous adsorption protection powder into the above solution for adsorption. Start stirring during the addition of the modified porous adsorption protection powder and adsorption. The stirring speed is 300r / min. After the addition is completed, continue stirring for 50 minutes to allow it to fully absorb the biological acid. Dry it using a spray drying process to obtain the first composite deodorizing alkaline powder.

[0074] a3. Add the first composite deodorizing alkaline powder to a solution containing 5% maleic acid and 3% zinc sulfate at a temperature of 35°C, and continue adsorption for 40 minutes. After adsorption, filter and irradiate the filtered solid with an electron beam at a dose of 50 kGy for 60 seconds, and then vacuum dry to obtain a composite deodorizing alkaline powder.

[0075] b. Preparation of composite powder for eliminating acid odor and senile odor b1. Add cysteine ​​and tea polyphenols in a mass ratio of 1:1 into deionized water to dissolve them, to obtain a solution with a concentration of 7%. The tea polyphenols are derived from plant extracts.

[0076] b2. Add the prepared modified porous adsorption protection powder into the above solution for adsorption. Start stirring during the addition of the modified porous adsorption protection powder and adsorption. The stirring speed is 300r / min. After the addition is completed, continue stirring for 50 minutes to allow it to be fully adsorbed. Use a spray drying process to dry it to obtain the first composite powder for eliminating acid odor and old age odor.

[0077] b3. Add the first composite acid and old age odor eliminating powder into a solution containing 3% of the cross-linking agent ethylene glycol diglycidyl ether at a temperature of 35°C, and continue adsorption for 30 minutes. After adsorption and filtration, cross-link the filtered solid at a reaction temperature of 40°C, a reaction time of 50 minutes, and a pH of 8.5. Then, vacuum dry the solid to obtain the final composite acid and old age odor eliminating powder.

[0078] c. The prepared composite alkaline deodorizing powder and the composite acidic and elderly deodorizing powder are mixed in a mass ratio of 1:1, and then lavender, an aromatic substance accounting for 15% of the total powder mass, is added for blending to prepare a composite deodorant.

[0079] The prepared antibacterial composite absorbent powder has an inhibition rate of 99.2% against Staphylococcus aureus, 99.5% against Escherichia coli, and 99.6% against Candida albicans; its ammonia reduction rate is 98.9%, acetic acid reduction rate is 99.3%, isovaleric acid reduction rate is 99.9%, and 2-nonenal reduction rate is 99.4%.

[0080] d. Add the prepared composite deodorant into deionized water with a mass fraction of 45%, and add 20% of the mass of the composite deodorant dispersant sodium dodecylbenzene sulfonate and 5% of the mass of the composite deodorant defoaming agent polyoxypropylene polyoxyethylene glycerol ether to the system. After stirring and mixing evenly, add the mixture into a high-speed disperser for dispersion at a speed of 2000 r / min. During the dispersion process, maintain the temperature at 20°C for 60 minutes. Then, add 6% of the mass of the composite deodorant as a thickener sodium carboxymethyl cellulose and mix well to obtain a composite deodorant dispersion.

[0081] The prepared composite deodorant dispersion was used to treat the fabric by a two-rolling and two-pressing process, with a bath ratio of 1:20, to obtain a deodorizing fabric. The fiber had an antibacterial rate of 87.5% against Staphylococcus aureus, 87.6% against Escherichia coli, and 88.9% against Candida albicans; its ammonia reduction rate was 83.9%, acetic acid reduction rate was 82.5%, isovaleric acid reduction rate was 93.2%, and 2-nonenal reduction rate was 81.6%.

[0082] Comparative Example 1 Compared with Example 1, in this comparative example, the porous material powder is prepared without using a silane coupling agent for treatment, and the other preparation steps are the same.

[0083] The prepared antibacterial composite absorbent powder has an inhibition rate of 96.1% against Staphylococcus aureus, 96.8% against Escherichia coli, and 95.9% against Candida albicans; its ammonia reduction rate is 93.2%, acetic acid reduction rate is 94.1%, isovaleric acid reduction rate is 96.8%, and 2-nonenal reduction rate is 95.6%.

[0084] The prepared composite deodorant is added into deionized water with a mass fraction of 35%, and the dispersant sodium dodecylbenzene sulfonate accounting for 15% of the mass of the composite deodorant and the defoaming agent polyoxypropylene polyoxyethylene glycerol ether accounting for 2% of the mass of the composite deodorant are added into the system. After stirring and mixing evenly, the mixture is added into a high-speed disperser for dispersion at a dispersion speed of 1500r / min. The temperature is maintained at 18°C ​​during the dispersion process for 90min. Then, the thickener sodium alginate accounting for 3% of the mass of the composite deodorant is added and mixed evenly to obtain a composite deodorant dispersion.

[0085] The prepared composite deodorant dispersion was added to the viscose fiber used in the wet spinning process through the pre-spinning injection process, and the addition amount was 6.0% (to cellulose methyl cellulose) according to the effective ingredients. Then, after cutting, washing, desulfurization, bleaching, oiling, drying and other processes, the viscose staple fiber with antibacterial and deodorizing functions of 1.67 dtex × 38 mm was obtained. The fiber has an antibacterial rate of 77.1% against Staphylococcus aureus, 79.2% against Escherichia coli, and 78.0% against Candida albicans; its ammonia reduction rate is 71.2%, acetic acid reduction rate is 72.0%, isovaleric acid reduction rate is 83.2%, and 2-nonenal reduction rate is 73.8%.

[0086] Comparative Example 2 Compared with Example 1, in this comparative example, hemicellulose is not used for treatment in the preparation of step 2) modified porous adsorption protection powder, and other preparation steps are the same.

[0087] The prepared antibacterial composite absorbent powder has an inhibition rate of 95.5% against Staphylococcus aureus, 96.1% against Escherichia coli, and 95.1% against Candida albicans; its ammonia reduction rate is 91.9%, acetic acid reduction rate is 93.2%, isovaleric acid reduction rate is 95.5%, and 2-nonenal reduction rate is 94.1%.

[0088] The prepared composite deodorant is added into deionized water with a mass fraction of 35%, and the dispersant sodium dodecylbenzene sulfonate accounting for 15% of the mass of the composite deodorant and the defoaming agent polyoxypropylene polyoxyethylene glycerol ether accounting for 2% of the mass of the composite deodorant are added into the system. After stirring and mixing evenly, the mixture is added into a high-speed disperser for dispersion at a dispersion speed of 1500r / min. The temperature is maintained at 18°C ​​during the dispersion process for 90min. Then, the thickener sodium alginate accounting for 3% of the mass of the composite deodorant is added and mixed evenly to obtain a composite deodorant dispersion.

[0089] The prepared composite deodorant dispersion was added to the viscose fiber used in the wet spinning process through the pre-spinning injection process, and the addition amount was 6.0% (to cellulose methyl) according to the effective ingredients. Then, after cutting, washing, desulfurization, bleaching, oiling, drying and other processes, the viscose staple fiber with antibacterial and deodorizing functions of 1.67 dtex × 38 mm was obtained. The fiber has an antibacterial rate of 75.9% against Staphylococcus aureus, 77.8% against Escherichia coli, and 76.7% against Candida albicans; its ammonia reduction rate is 70.1%, acetic acid reduction rate is 69.2%, isovaleric acid reduction rate is 81.0%, and 2-nonenal reduction rate is 71.1%.

[0090] Comparative Example 3 Compared with Example 1, this comparative example uses only amino acids in b, preparing the composite powder for eliminating acid odor and senile odor, and the persimmon tannin in b1, and the other preparation steps are the same.

[0091] The prepared antibacterial composite absorbent powder has an inhibition rate of 98.2% against Staphylococcus aureus, 98.5% against Escherichia coli, and 97.6% against Candida albicans; its ammonia reduction rate is 96.3%, acetic acid reduction rate is 96.9%, isovaleric acid reduction rate is 99.2%, and 2-nonenal reduction rate is 93.5%.

[0092] The prepared composite deodorant is added into deionized water with a mass fraction of 35%, and the dispersant sodium dodecylbenzene sulfonate accounting for 15% of the mass of the composite deodorant and the defoaming agent polyoxypropylene polyoxyethylene glycerol ether accounting for 2% of the mass of the composite deodorant are added into the system. After stirring and mixing evenly, the mixture is added into a high-speed disperser for dispersion at a dispersion speed of 1500r / min. The temperature is maintained at 18°C ​​during the dispersion process for 90min. Then, the thickener sodium alginate accounting for 3% of the mass of the composite deodorant is added and mixed evenly to obtain a composite deodorant dispersion.

[0093] The prepared composite deodorant dispersion was added to the viscose fiber used in the wet spinning process through the pre-spinning injection process, and the addition amount was 6.0% (to cellulose methyl cellulose) according to the effective ingredients. Then, after cutting, washing, desulfurization, bleaching, oiling, drying and other processes, the viscose staple fiber with antibacterial and deodorizing functions of 1.67 dtex×38 mm was obtained. The fiber has an antibacterial rate of 81.5% against Staphylococcus aureus, 82.3% against Escherichia coli, and 83.5% against Candida albicans; its ammonia reduction rate is 79.3%, acetic acid reduction rate is 76.7%, isovaleric acid reduction rate is 88.6%, and 2-nonenal reduction rate is 72.2%.

[0094] Of course, the above contents are only preferred embodiments of the present invention and cannot be considered to limit the scope of the embodiments of the present invention. The present invention is not limited to the above examples, and equal changes and improvements made by ordinary technicians in the technical field within the essential scope of the present invention should all fall within the scope of the patent coverage of the present invention.

Claims

1. A method for preparing a composite deodorant, characterized in that: The following steps are involved: a. Preparation of composite alkaline deodorizing powder a1. Add one or more of alginic acid, lactic acid and chlorogenic acid into water at 25-30°C to dissolve the solution to obtain a solution with a mass concentration of 4%-6%; a2. Add the modified porous adsorption protection powder to the solution of step a1, stir and adsorb, and spray dry to obtain a first composite deodorizing alkaline powder; a3. Add the first composite deodorizing alkaline powder to a solution containing 3%-5% polycarboxylic acid and 1%-3% zinc salt at a temperature of 25°C-35°C, adsorb for 30-40 minutes, filter, irradiate the solid with electron beam, and vacuum dry to obtain a composite deodorizing alkaline powder; b. Preparation of composite powder for eliminating acidic odor and senile odor b1. Mix one or more of amino acids, tannins, and polyphenols, add them into water and dissolve them to obtain a solution with a mass concentration of 5% to 7%; b2, adding the modified porous adsorption protection powder to the solution of step b1, stirring and adsorbing, and spray drying to obtain the first composite powder for eliminating acid odor and senile odor; b3. Add the first composite deodorizing and acid odor removing powder to a solution of 1.5%-3% ethylene glycol diglycidyl ether or glutamine aminotransferase at a temperature of 25°C-35°C, adsorb for 20min-30min, filter, and cross-link the solid at a reaction temperature of 30°C-40°C, a reaction time of 50min-70min, and a pH of 7.0-8.

5. After the reaction, vacuum dry to obtain a composite deodorizing and acid odor removing powder; c. Mix the prepared composite alkaline deodorizing powder with the composite acidic deodorizing and old age deodorizing powders to prepare a composite deodorant.

2. The method for preparing the composite deodorant according to claim 1, characterized in that: In step c, the prepared composite alkaline deodorizing powder is mixed with the composite acidic deodorizing and old age deodorizing powders to prepare a final composite deodorant.

3. The method for preparing the composite deodorant according to claim 1, characterized in that: The modified porous adsorption protection powder is prepared according to the following steps: (1) spray-drying an inorganic porous material dispersion or a β-cyclodextrin organic porous material dispersion to obtain a porous material powder; (2) dissolving hemicellulose and / or polypeptide in ionic liquid to obtain a mixed solution with a mass concentration of 2-5%; (3) Add the porous material powder of step (1) to the mixed solution of step (2), stir and mix, filter, add water, and spray dry to obtain a modified porous adsorption protection powder.

4. The method for preparing the composite deodorant according to claim 3, characterized in that: The inorganic porous material dispersion in step (1) is prepared by grinding the inorganic porous material powder to a particle size D90≤3.350 μm, adding a silane coupling agent after dispersion, and uniformly dispersing the powder; the inorganic porous material powder is one of activated carbon, binchotan, silica gel, zeolite, and silicate minerals; and the amount of the silane coupling agent added is 10%-15% of the mass of the inorganic porous material powder.

5. The method for preparing the composite deodorant according to claim 3, characterized in that: The mass concentration of the inorganic porous substance powder in the inorganic porous substance dispersion is 30%-50%; the mass concentration of β-cyclodextrin in the β-cyclodextrin organic porous substance dispersion is 30%-50%.

6. The method for preparing the composite deodorant according to claim 3, characterized in that: In step (2), the degree of polymerization of hemicellulose is 50-80; the molecular weight of the polypeptide is 5000-10000; the ionic liquid is an alkyl imidazole type ionic liquid, wherein the cation is one of ethyl and butyl; the anion is Cl - 、SCN - One of them.

7. The method for preparing the composite deodorant according to claim 3, characterized in that: The spray drying parameters in step (1) and step (3) are: inlet air temperature 150°C-180°C, outlet air temperature 95°C-105°C, and feed rate 15mL / min-25mL / min.

8. A composite deodorant, characterized in that: The composite deodorant is prepared by the preparation method of the composite deodorant according to any one of claims 1 to 7.

9. An application of the composite deodorant according to claim 8, characterized in that: The prepared composite deodorant is used in synthetic fibers for melt spinning, or the composite deodorant is used to make a composite deodorant dispersion for use in chemical fibers for wet spinning, or the composite deodorant dispersion is directly applied to fabrics and the fabrics are treated by a padding process.

10. The use of the composite deodorant according to claim 9, characterized in that: The specific steps of using the composite deodorant to prepare the composite deodorant dispersion are as follows: adding the prepared composite deodorant into water with a mass fraction of 35%-45%, adding a dispersant accounting for 15%-20% of the mass of the composite deodorant and a defoamer accounting for 2%-5% of the mass of the composite deodorant, stirring and mixing evenly, dispersing, and then adding a thickener accounting for 3%-6% of the mass of the composite deodorant, stirring evenly, and preparing the composite deodorant dispersion; the dispersion speed is 1500r / min-2000r / min, the temperature is maintained at 18°C-20°C during the dispersion process, and the dispersion time is 60min-90min.

Citation Information

Patent Citations

  • Antibacterial deodorizing tea-residue-modified functional cotton sock and production method thereof

    CN110344236A

  • Antibacterial, deodorizing, skin-care and health-care cellulose fiber and preparation method thereof

    CN114182379A

  • Fibrilia with antibacterial and deodorizing functions and preparation method thereof

    CN114182528A

  • Deodorizing composite functional polyamide fiber and preparation method thereof

    CN117468115A

  • Composite particle, production method of the same, and personal care product including the same

    JP2021176827A